Capturing the Mood: Facebook and Fast-to-Face Encounters in the Workplace - Mark, Gloria; Iqbal, Shamsi; Czerwinski, Mary; Johns, Paul (Proceedings of CSCW 2014, 2014)
What makes people happy, engaged and feeling challenged at work? We conducted an in situ study of Facebook and face-to-face interactions examining how they influence people's mood in the workplace. Thirty-two participants in an organization were each observed for five days in their natural work environment using automated data capture and self-report measures. Our results show that online and offline social interactions are associated with different mood experiences, suggesting that they serve different purposes at work. Face-to-face interactions are associated with a happy mood throughout the day whereas Facebook use and being engaged in work contribute to an overall positive feeling at the end of the day. Email use is associated with negative affect and along with multi-tasking, it is associated with a feeling of engagement and challenge throughout the day. This is the first study that examined how offline and online social interactions influence mood in the workplace.